Prospective Cohort Study of Performance Status and Activities of Daily Living After Surgery for Spinal Metastasis. Issue 8 (October 2017) - Kakutani, Kenichiro; Sakai, Yoshitada; Maeno, Koichiro; Takada, Toru; Yurube, Takashi; Kurakawa, Takuto; Miyazaki, Shingo; Terashima, Yoshiki; Ito, Masaaki; Hara, Hitomi; Kawamoto, Teruya; Ejima, Yasuo; et al.
Abstract : Study Design: A prospective cohort study of performance status (PS) and activities of daily living (ADL) in patients with spinal metastasis. Objective: To identify the effect of spinal surgery on PS and ADL in patients with spinal metastasis. Summary of Background Data: Spinal metastasis causes severe neurological deficits, resulting in drastic loss of patients' PS and ADL. However, the effect of spine surgery on PS and ADL is not well known. Materials and Methods: Seventy patients with spinal metastasis were enrolled in this study. Forty-six patients desired and underwent spine surgery ("surgery" group) and 24 patients did not desire surgery ("nonsurgery" group). Both groups received optimal treatments, including radiation, chemotherapy, and palliative care services. Evaluation was performed at 1, 3, and 6 months after study enrollment using the Eastern Cooperative Oncology Group PS, the Barthel index (BI) for ADL, and Frankel classification for neurological status. Results: There was no significant difference in baseline PS, the BI, or Frankel classification between the groups. The surgery group showed significant improvement in PS, maintaining grade 2 or less throughout the duration of the study, as well as in ADL, exceeding 70 points of the BI, compared with the nonsurgery group ( P <0.05). Significantly improved neurological condition was also observed in the surgery group over the following 6 months. More than 95% of patients who underwent surgery improved their PS, the BI, and neurological status. Furthermore, >80% of these patients maintained improvement in PS, the BI, and neurological status for at least 6 months. In contrast, PS, the BI, and neurological status of patients in the "nonsurgery" group deteriorated throughout the study period. Conclusions: Spine surgery improves PS, ADL, and neurological status in patients with spinal metastasis for a minimum 6 months. This indicates that these patients can acquire an independent daily life.